Intranodal palisaded myofibroblastoma – a rare case report and literature review. Issue 10 (8th August 2016) - Karabulut, Yasemin Yuyucu; Kara, Tuba; Berkeşoğlu, Mustafa
Abstract : Intranodal palisaded myofibroblastoma (IPM) is a benign mesenchymal neoplasm originating from smooth muscle cells and myofibroblasts. The inguinal region is the most common site of this rare tumor. As there are only about 89 such cases reported in the literature, the precise etiology and pathogenesis have yet to be explained adequately. It is characterized by spindle cells, amianthoid fibers, and by the proliferation of hemosiderin‐containing histiocytes in the lymph node. A nodular lesion was excised from the inguinal region of a 47‐year‐old female patient with the clinical diagnosis of lymphoma and/or metastase. Macroscopic examination of a section of the lesion demonstrated a solid appearance. Microscopic examination revealed spindle‐cell proliferation, amianthoid fibers, hemosiderin pigment, and extravasated erythrocytes. Nuclei of the spindle cells displayed a palisaded appearance. Compressed lymphoid tissue was observed around the lesion. Neoplastic cells were identified by the presence of vimentin, SMA, Cyclin D1, and beta‐catenin. The Ki67 index was less than 1%. Histological examination confirmed the diagnosis of IPM. Although IPM is benign, it is frequently confused with metastatic lesions and lymphomas.